New Mutations in GyrA Gene of Escherichia Coli Isolated form Iraqi Patients - Al-Fayyadh, Ziyad Hameed; Turkie, Ahmed Muhammed; Al-Mathkhury, Harith Jabbar Fahad (Iraqi Journal of Science, 2022)
The present study included a collecting of 165 specimens form different sources,93 isolates were identified as Escherichia coli depending on morphological andbiochemical tests in addition to automated systems such as VITEK 2 and api 20E.All isolates under study developed high resistance toward cefotaxime, ceftazidime,ceftriaxone, and ciprofloxacin estimated by minimum inhibitory concentration. Stooland wound specimens characterized by harbouring the highest resistant isolates in apercentage reached 100% against antibiotics under study. Insignificant differenceswere found between isolates collected from males and females. Upon using diskdisplacement method to detect extended spectrum beta lactamases (ESBL), it wasfound that 37.73% of isolates were ESBL producers. However, stool and urinespecimens harboured the highest percentage of producers. The present studyfindings revealed a presence of efflux pump in 77.5% of tested isolates usingcartwheel method. Nevertheless, PCR technique exposed about 85% of isolatesharboured acrAB efflux pump gene. Moreover, the results of this study illustratedthat all isolates contained gyrA and parC using PCR technique. Accordingly, threeisolates were chosen for nucleotide alignment study; one of them is sensitive and theother two are resistant to ciprofloxacin (acrAB free). The results showed a presenceof stable and frequent three mutations in the resistant isolates (14 and 3). Atransition mutation found in the site 4808116 in which guanine is replaced byadenine. Furthermore, two transversion mutations were located in 4804221 and4808222 sites. Additionally, a hot spot was detected in the site 4808109.